2005
DOI: 10.1007/s10522-005-4810-6
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Hormone Replacement Therapy in Normalizing Age Related Neuronal Markers in Different Age Groups of Naturally Menopausal Rats

Abstract: Aging of the normal brain is accompanied by changes in its structure, function, and metabolism. There are significant gender differences in aging brain. Most of these changes increase during menopausal condition in females when the level of estradiol and progesterone are decreased. The objective of this study was to determine the effect of estradiol and progesterone (separate as well as combined) hormones in neuronal tissues from naturally menopausal rats of different age groups. Results show decreased activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2008
2008
2013
2013

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 50 publications
1
22
0
Order By: Relevance
“…Earlier studies have revealed that there is an increase in the lipid peroxides of aged liver and brain homogenates (Miyazawa et al 1993). Lipid peroxide levels were found to be significantly higher in brains of 18 months old as compared to 4 months old rats (Noda et al 1982;Moorthy et al 2005).…”
Section: Introductionmentioning
confidence: 88%
See 1 more Smart Citation
“…Earlier studies have revealed that there is an increase in the lipid peroxides of aged liver and brain homogenates (Miyazawa et al 1993). Lipid peroxide levels were found to be significantly higher in brains of 18 months old as compared to 4 months old rats (Noda et al 1982;Moorthy et al 2005).…”
Section: Introductionmentioning
confidence: 88%
“…The accumulation of lipofuscin in cells occurs because it is undegradable and cannot be removed from the cells via exocytosis. As age progresses, the lipofuscin content per neuron as well as the number of pigmented neurons has been shown to increase in a linear fashion in many regions of the brain (Sharma et al 1993;Drach et al 1994;Moorthy et al 2005). Intraneuronal accumulation of lipofuscin is considered to be a marker of neuronal aging, and its formation appears to be integrative and proportional to the occurrence of lipid peroxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Percentage changes in the activities of NADP linked, glycolytic and membrane associated enzymes from synaptosomes prepared from cerebral hemispheres of aging rat brain taking 20 days old as 100%. Figure derived from Baquer et al (1990) Earlier work and ample evidence has shown that peroxidative damage to lipid and protein occurs with the aging process and the products of these reactions accumulate in the brain with age (Bondereff 1964;Mann and Yates 1974;Davison and Wright 1980;Baquer et al 1990;Moorthy et al 2004aMoorthy et al , 2005aBala et al 2006;Sinha et al 2005Sinha et al , 2008.…”
Section: Age Related Changes In Brain Parametersmentioning
confidence: 99%
“…K ? ATPase Moorthy et al 2004aMoorthy et al , 2005aSiddiqui et al 2005) both enzymes controlling the polarization of neurons.…”
Section: Age Related Changes In Brain Parametersmentioning
confidence: 99%
See 1 more Smart Citation